I) \( 27 \div 3+[66 \div 6-(28 \div 14 \times 2)+30 \div 6]-10= \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Beyond the Answer
First, let's break down the expression step by step. 1. Start with the operations inside the brackets: - \( 66 \div 6 = 11 \) - \( 28 \div 14 = 2 \), then \( 2 \times 2 = 4 \) - \( 30 \div 6 = 5 \) Now substitute these results back into the expression: \[ 27 \div 3 + [11 - 4 + 5] - 10 \] 2. Calculate \( 27 \div 3 = 9 \). 3. Now solve inside the brackets: - \( 11 - 4 + 5 = 11 - 4 = 7 \) - Then \( 7 + 5 = 12 \) 4. Now plug this back into the expression: \[ 9 + 12 - 10 \] 5. Finally, calculate: - \( 9 + 12 = 21 \) - Then \( 21 - 10 = 11 \) Thus, the final result is \( \boxed{11} \).